Thermal conductivity of supraglacial volcanic deposits in Iceland - Möller, Rebecca; Römer, Wolfgang; Möller, Marco; Wollenberg, Uwe; Lehmkuhl, Frank; Schneider, Christoph; Kukla, Peter A. (International Journal of Earth Sciences, 2020)
Abstract Supraglacial deposits of tephra or volcaniclastics have the potential to cause significant anomalies of glacier ablation and runoff. The intensity of these anomalies is governed by the thermal resistivity of the covering layer and hence the thermal conductivity of the deposited grains. This study concentrates on causal and quantitative relationships between density, geochemical composition and thermal conductivity of volcanic materials based on the analysis of 43 samples from locations across Iceland. Thermal conductivity is primarily influenced by density, whereas geochemical composition has been proved to be of subsidiary importance. Four different multiple regression models were calibrated that calculate the grain thermal conductivity of a volcanic material based on rock properties and geochemical composition. In a subsequent step, the bulk thermal conductivity of the respective deposit is calculated as a function of porosity and degree of water saturation. Examples using volcanic material from the Eyjafjallajökull 2010 and Grímsvötn 2011 eruptions confirm that the presented calculation scheme can be executed using only limited geochemical data as input. This facilitates an easy application of the modeling scheme immediately after a volcanic eruption.